METHODOLOGY FOR COMPILING AND CONDUCTING CLASSES ON THEATRICAL ACTIVITIES IN PRESCHOOL EDUCATIONAL ORGANIZATIONS (American Journal of Research in Humanities and Social Sciences, 2023)
This article reveals the methods for compiling and conducting classes on theatrical activities in preschool educational organizations. The definition of such concepts as "theater", "theatrical activity" and "theatrical game" is given.